THE TRANSFORMATION OF BANKING INTERMEDIATION THEORY IN THE CONTEXT OF FINTECH AND DECENTRALIZED FINANCE (DEFI) - Rajib Dewan Chakma (CV. Fahr Publishing, 2025)
This study aims to conceptualize a new theoretical framework for financial intermediation in response to the rise of Financial Technology (FinTech) and Decentralized Finance (DeFi), which have introduced structural and functional changes to the traditional role of banks. Classical intermediation theory, which emphasizes delegated monitoring, liquidity transformation, and maturity transformation, is increasingly insufficient to explain emerging hybrid and disintermediated financial systems. This research adopts a qualitative library-based method, using thematic literature analysis from peer-reviewed academic journals, institutional reports, and policy papers published between 2017 and 2025. The findings reveal that intermediation functions are no longer confined to traditional institutions; instead, they are distributed across smart contracts, decentralized protocols, and algorithmic platforms. A key novelty of this study lies in the articulation of “protocolised intermediation,” a concept that captures the convergence of centralized banking and decentralized architectures into hybrid financial models. The analysis also introduces a dual-axis framework to categorize intermediation based on levels of decentralization and functional transformation. Furthermore, the research synthesizes recent insights on risk governance, regulatory arbitrage, and digital trust, positioning them as critical variables in the theoretical evolution of intermediation. In conclusion, the study offers a reconceptualized understanding of intermediation theory, aligning it with the realities of the post-classical, algorithm-driven financial ecosystem. This contribution is expected to support further academic exploration and inform global financial policy debates.